Response of Canada geese to a dead goose effigy - Seamans, Thomas W.; Bernhardt, Glen E. (eScholarship, University of California, 2004)
The North American Canada goose population increased at a rate of 10.5% per year, 1966 - 2001. Canada geese rank as the third most hazardous species in regards to collisions with aircraft. Sound Canada goose management tools are critical for a safer airport environment. We conducted field evaluations of a Canada goose effigy during the breeding season with territorial pairs and in late summer with post-fledging flocks to determine if geese were deterred by the effigy. No difference in territorial pairs was found between pretreatment and treatment periods for Canada geese when goose effigies were placed within their territories. In post-fledging flocks, the mean number of geese observed during pretreatment (74.9 ± 12.9), treatment (14.8 ± 4.5), and posttreatment (53.6 ± 14.2) periods differed (P < 0.01). There was no difference (P = 0.56) between the mean number of geese observed during a second round of 5-day pretreatment (58.7) and 5-day second round treatment (43.7) periods. By itself, the goose effigy was not effective as a Canada goose deterrent after approximately 5 days. However, this effigy may have some potential in an integrated goose control program conducted outside of the breeding season. Further evaluation of the effigy as part of an integrated Canada goose control program is recommended.